Modified atmospheric processing and packaging of fish : (Blackwell Pub, 2006)
The book has been made possible through the support and hard work of program and persons that deserve special recognition: The conference that assembled the expertise was organized in collab-oration with the National fisheries Institute; The US Department of Agriculture provide support funds for the conference and portions of the ressearch through the grant; The compilation of the book was support by the NOAA, the views expressed herein do not necessarily reflect the views of any of these organizations; Zina Williams, food science and human nutrition Dept., University of Florida, deserves specific recognition for her support in compiling the entire manuscript.